Forestry and caribou in British Columbia - Stevenson, Susan K. (Rangifer, 1991)
Forest harvesting in mountain caribou range has been an issue for many years. Radiotelemetry studies on mountain caribou in the last decade have helped identify the geographic areas of conflict, improved understanding of the mechanisms by which forestry activities affect caribou, and suggested new approaches to management. Forest harvesting has begun to impact population of northern caribou, and researchers have begun to examine those impacts. Interest in integrating forest management and caribou habitat management has increased and has manifested itself in two ways: experimentation with special stand management practices intended to maintain or create caribou habitat, and the creation of tools to help managers make decisions in a landscape context.